Pengembangan Literasi Ekonomi Masyarakat Desa Maryke dalam Meningkatkan Kesejahteraan melalui Pemanfaatan Sumber Daya Lokal - M. Alfin Muttaqin; Isman Efendi Limbong (Bumi: Jurnal Hasil Kegiatan Sosialisasi Pengabdian kepada Masyarakat, 2024)
The Economic Literacy Development Program for Maryke Village aims to improve community welfare through the utilization of local resources, particularly in managing small businesses like broomstick production. The community’s limited understanding of economic literacy has hindered their ability to manage finances and optimize local economic potential. This research employs a qualitative methodology with a participatory approach, collecting data through observations, in-depth interviews, and group discussions with the community and local stakeholders. The results indicate that the program successfully enhanced the community’s understanding of economic literacy, particularly in financial management and business planning. Participants of the program began to manage household budgets, save regularly, and develop local resource-based businesses. Increased productivity and income were observed in the broomstick production business after the training. The program not only improved the community's awareness of the importance of economic literacy but also encouraged them to use local resources more effectively and sustainably, leading to a positive impact on their welfare.